Estimating Financing Needs for Local Services in Madagascar - Febgler, Wolfgang (World Bank, Washington, DC, 2012)
This note presents the methodology and findings of a field study on the financing needs of Madagascar's communes-the country's lowest but most institutionally advanced level of subnational government. Following a first round of municipal elections in 1995, more than 1,500 communes are now formally responsible for maintaining basic administrative services and social and economic infrastructure, including local waste disposal and sanitation. In addition, communes are responsible for identifying and coordinating local investments and for supporting implementation of the national Poverty Reduction Strategy at the local level.